Adição do resíduo de biomassa da cana-de-açúcar em pastas para cimentação de poços petrolíferos produtores de óleos pesados - Anjos, Marcos Alyssandro Soares dos (2009)
The Potiguar basin has large fields of viscous oil where the used method for recovering is based on vapor injection; this operation is carried out by injecting vapor in the oilwell directly, without the protection of a revetment through thermal insulation, what causes its dilation and, consequently, cracks in the cement placed on the annular, and lost of hydraulic insulation; this crack is occasioned by the phenomenon of retrogression of the compressive resistance due to the conversion of the hydrated calcium silicate in phases calcium-rich, caused by the high temperatures in the wells, subjected to thermal recuperation. This work has evaluated the application of composite pastes with addition of residue of biomass of ground sugar-cane bagasse as anti-retrogression mineral admixture for cementation of oil-wells subjected to thermal recuperation. The addition of the mineral residue was carried out considering a relative amount of 10, 20, 30, 40 and 59% in relation to cement mass, trying to improve the microstructure of the paste, still being developed a reference paste only with cement and a paste with addition of 40% of silica flour - renowned material in the oil industry as anti-retrogression additive. Pozzolanic activity of the ash was evaluated through XRD, TG/DTG, as the resistance to compression, and it was also determined the physical and mechanical behavior of the pastes when submitted to cure at low temperatures (22 and 38º C); besides it was evaluated the behavior of the pastes when submitted to two cycles of cure at high temperature (280ºC) and pressure (7 MPa). It was verified that the ash of the sugar-cane biomass presents pozzolanic reaction and has great efficiency in decrease the permeability of the paste by filler effect, as well as that addition of ash in a relative amount of 10, 20 e 30% increases cured compressive resistance at low temperatures. It was also showed that the ash in a relative amount of 40% and 59% has very significant efficiency as anti-retrogression additive, since it prevents the decrease of compressive resistance and forms hydrated calcium silicate type xenotlita and tobermorita which have more resistance and stability in high temperatures